1981
DOI: 10.1099/00222615-14-3-321
|View full text |Cite
|
Sign up to set email alerts
|

Haemolysis by urinary Escherichia coli and virulence in mice

Abstract: PLATE XVIIISUMMARY. The influence of haemolysin production on virulence was studied in an experimental mouse model. Urinary strains of Escherichia coli can be divided into three virulence groups by determining their kinetics in the mouse kidney after intravenous injection. Virulent strains of groups I1 and I11 were more often haemolytic than avirulent group-I strains. Haemolytic virulent strains often caused haemoglobinuria in the mice, and killed the mice more rapidly than did non-haemolytic virulent strains.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

1981
1981
1988
1988

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 25 publications
1
29
0
Order By: Relevance
“…The type B2 could be considered as a molecular marker of virulence, but it is not known whether esterase type B2 contributes directly or indirectly to the disease process or whether it is only associated with virulence factors. To evaluate this association, we have correlated types B1 and B2 with a-haemolysin and MRHA, which have been well documented as virulence factors (Hagberg et al 1981;Van den Bosch et al 1981;Welch et al 1981; Gadeberg, Orskov & Rhodes, 1983;Hacker et al 1983;Cavalieri, Bohach & Snyder, 1984) and considered to be genotypically linked (Berger et al 1982;Low et al 1984). The proportion of type B1 strains and type B2 strains producing a MRHA were comparable in septicaemia (28 and 68 %, respectively) to those found in an earlier study (30 and 70°%, respectively) (Goullet & Picard, 1986b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The type B2 could be considered as a molecular marker of virulence, but it is not known whether esterase type B2 contributes directly or indirectly to the disease process or whether it is only associated with virulence factors. To evaluate this association, we have correlated types B1 and B2 with a-haemolysin and MRHA, which have been well documented as virulence factors (Hagberg et al 1981;Van den Bosch et al 1981;Welch et al 1981; Gadeberg, Orskov & Rhodes, 1983;Hacker et al 1983;Cavalieri, Bohach & Snyder, 1984) and considered to be genotypically linked (Berger et al 1982;Low et al 1984). The proportion of type B1 strains and type B2 strains producing a MRHA were comparable in septicaemia (28 and 68 %, respectively) to those found in an earlier study (30 and 70°%, respectively) (Goullet & Picard, 1986b).…”
Section: Discussionmentioning
confidence: 99%
“…some 0 and K antigens (Orskov et al 1977; Orskov & Orskov, 1985), resistance to serum bactericidal activity (Taylor, 1983;Cross et al 1986), virulence to mice and to chicken embryo (Minshew et al 1978; Van den Bosch, De Graaff & MacLaren, 1979; Bosch, Emody & Ketyi, 1982), aerobactin production (Carbonetti et al 1986), a-haemolysin production (Van den Bosch et al 1981;Welch et al 1981;Cavalieri, Bohach & Snyder, 1984) and mannose resistant haemagglutinin (Evans et al 1980;Hagberg et al 1981;Vaisanen et al 1981). However, these infections not only depend on the intrinsic properties of the strains but also on various hostdependent factors, such as susceptibility linked to an underlying disease (Singer, * Author for reprints.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Em6dy et al (1980) could not demonstrate a substantial difference between cultures producing haemolysin and their non-haemolytic derivatives in mice, and van den Bosch et al (1981) also reported that haemolysin was not an important virulence factor in the extremely virulent group III strains which had a more general virulence for mice.…”
Section: Haemolysinmentioning
confidence: 98%
“…However, strains of some 0: K: H serotypes within these 0 groups are more often haemolytic than others (Vahlne, 1945;Sj6stedt, 1946). Van den Bosch et al (1981) studied the influence on virulence of haemolysin production in the experimental mouse model mentioned above, which involves intravenous injection of the bacteria (van den Bosch, de Graaf & MacLaren, 1979). They concluded that haemolysin production was a decisive virulence factor in most of the mouse nephropathogenic strains, called group II strains, since 6 out of 7 strains became avirulent after elimination of the ability to produce haemolysin.…”
Section: Haemolysinmentioning
confidence: 99%